2020
DOI: 10.3390/ijms21155363
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Proteome of Fibroblasts Isolated from Psoriatic Skin Lesions

Abstract: The dermal fibroblasts are in constant contact with the cells of the immune system and skin epidermis. Therefore, they are essential for the development of lesions in psoriasis. The aim of this study was to assess the changes in the proteomic profile of fibroblasts in the dermis of psoriasis patients, and to discuss the most significant changes and their potential consequences. The proteomic results indicate that fibroblast dysfunction arises from the upregulation of proinflammatory factors and antioxidant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 101 publications
(139 reference statements)
0
32
1
Order By: Relevance
“…It has been shown to prevent 4-HNE-protein and MDA-protein adduct levels in fibroblasts irradiated with UV [18]. In this way, CBD protects lipids and proteins involved in cellular signaling pathways from oxidative effects [19,20]. The purpose of this study was to evaluate the mechanism of CBD action with respect to redox imbalance in keratinocytes of rat skin exposed to chronic UVA or UVB radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to prevent 4-HNE-protein and MDA-protein adduct levels in fibroblasts irradiated with UV [18]. In this way, CBD protects lipids and proteins involved in cellular signaling pathways from oxidative effects [19,20]. The purpose of this study was to evaluate the mechanism of CBD action with respect to redox imbalance in keratinocytes of rat skin exposed to chronic UVA or UVB radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The molecules significantly reduced the mRNA expression of all pro-inflammatory cytokines ( Figure 7 f). In addition, we proceeded to explore the beneficial effects in a 3D full-thickness human skin model that better mimics psoriatic skin for the presence of fibroblasts harvested from lesions, which have been previously shown to exert a relevant role in pathogenesis of psoriasis [ 54 , 55 , 56 , 57 , 58 , 59 ]. The treatment with both compounds enhanced the differentiation process as assessed by the epidermal thinning associated with stratum corneum thickening and by the increased expression of filaggrin.…”
Section: Resultsmentioning
confidence: 99%
“…The second system represents an optimized model of psoriasis that better mimics the in vivo psoriatic skin phenotype due to the presence of fibroblasts isolated from psoriatic skin lesions. Some studies demonstrated significant changes in the proteomic profile of psoriatic fibroblasts responsible for the upregulation of growth factors, bioactive mediators, and pro-inflammatory cytokines which promote and sustain the hyperproliferation of keratinocytes and the inflammatory status [ 55 , 57 , 59 , 73 ]. In 3D systems maintained in basal conditions, FICZ, differently from our molecules, induced mild signs of chloracne phenotype such as the thickening of the stratum corneum and the epidermal thinning.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight the broad pro-inflammatory capacity of dermal fibroblasts. Interestingly, proteomic analysis of fibroblasts from psoriatic patients confirms higher levels of inflammation-associated proteins, such as TNFα [ 99 ] and supernatant from psoriatic fibroblasts induces an inflammatory macrophage phenotype [ 100 ]. Additionally, fibroblasts from atopic dermatitis patients induce inflammatory gene expression in cultured skin equivalents [ 101 ].…”
Section: Contribution Of Fibroblasts To Injury-induced Inflammatiomentioning
confidence: 99%